A imagem discursiva do rap e sua influência em alunos das séries finais do ensino médio em escolas da periferia - Silva, Rosmeiri Aparecida Rodrigues da (2011)
This paper discusses an analysis of the discursive practices of the rap group Racionais MC's, being one of the pioneering groups in this genre is respected and admired by many, mainly young people from the suburbs of large cities. Based on the concepts of discourse analysis in the perspective of Maingueneau Dominique (2008) chose to work with the following plans of the Global Semantic proposed by the author: the scenery, the discursive ethos and interdiscursivity. Given these considerations our overall goal was to show how the set designs were built and the construction of the ethos of the rapper's outskirts. And as a specific goal to show how the ethos manifested in three selected rap lyrics reveals the identification between young adults living in the suburbs of Greater Sao Paulo and the discourse in this statement of the group's rappers Racionais MC's